1999
DOI: 10.1093/tropej/45.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breastfeeding in very low birthweight infants at the time of discharge from hospital

Abstract: In a case-control study carried out in the Kuala Lumpur Maternity Hospital between 1st July 1995 and 31st January 1996 the objectives were (1) to determine the rate of breastfeeding in surviving very low birthweight (VLBW, < or = 1500 g) Malaysian infants following the introduction of the Baby Friendly Hospital Concept, and (2) to identify significant predictors associated with successful breastfeeding in these infants. During the study period, 201 (1.24 per cent) of live-born infants were VLBW infants, 192 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
2
14
2
4
Order By: Relevance
“…Nesta pesquisa, não houve associação significativa relativa ao grau de escolaridade materno, diferentemente dos resultados de outro estudo, que apontou maior prevalência de amamentação na alta hospitalar de recém-nascidos de muito baixo peso cujas mães tinham maior grau de instrução escolar 12 .…”
Section: Discussionunclassified
“…Nesta pesquisa, não houve associação significativa relativa ao grau de escolaridade materno, diferentemente dos resultados de outro estudo, que apontou maior prevalência de amamentação na alta hospitalar de recém-nascidos de muito baixo peso cujas mães tinham maior grau de instrução escolar 12 .…”
Section: Discussionunclassified
“…Bicalho-Mancini et al, 71 in a study about the risk factors of not exclusively breastfeeding LBW infants at an NICU in Belo Horizonte, state of Minas Gerais, before and after the implementation of the Baby Friendly Hospital Initiative, found that, although the rates of exclusive breastfeeding at hospital discharge increased from 36% (before implementation) to 54.7% (after implementation), these figures show the necessity of other interventions in order to encourage the breastfeeding of these babies. Boo,72 in Malaysia, with the aim of determining the breastfeeding rate among babies weighing less than 1,500 g admitted to a high-risk neonatal unit, observed that, despite breastfeeding incentive programs adopted by the hospital, only 40.2% of these babies were being breastfed at the time of hospital discharge.…”
Section: Evidence Of Benefits Related To the Breastfeeding Practicementioning
confidence: 99%
“…The commonly used conventional indicators are physiological stability, weight greater than or equal to 1,500 g, gestational age greater than or equal to 34 weeks and ability to ingest the whole volume of milk indicated in the bottle. 8,42,107 However, by choosing weight, gestational age or ability to suck at the bottle, there is a risk of delaying suction directly at the breast. 60 Ideally, the following aspects should also be taken into consideration: behavioral criteria, how to suck at the nasogastric tube, showing rooting reflex during skin-toskin contact, and staying alert, considering the observations of mothers and nurses.…”
Section: Special Considerations For Human Milk Feeding Of Preterm Infmentioning
confidence: 99%